Nanostructured Drug Delivery Systems for Targeting 5-α-Reductase Inhibitors to the Hair Follicle - Silvia Tampucci; Valentina Paganini; Susi Burgalassi; Patrizia Chetoni; Daniela Monti (MDPI AG, 2022)
Androgenetic alopecia is a multifactorial condition characterized by noticeable hair loss, affecting both men and women and representing a debilitating and chronic disorder that considerably affects the quality of life. Available topical treatments based on minoxidil or finasteride require repeated applications and are associated with a certain number of adverse effects. The challenges associated with current treatments pave the way for the research of new therapeutic strategies, more precise and selective, and capable of providing long-term results. In this context, the present review examines the new proposed formulation strategies to deliver 5-α-reductase inhibitors in order to obtain a targeted drug delivery, for improving drug retention at the site of action in the hair follicle, contemporaneously reducing drug systemic absorption, which is the cause of important adverse effects. In particular, the research will be focused on the several aspects that influence the performance of nanostructured drug delivery systems in creating a depot in the hair follicles, such as particle size, surface charge, excipients, and combined application with external stimuli (infrared radiation, mechanical massage, ultrasounds application).